TERBAIC (Team-Based Learning And Hypnocaring) As A Strategy To Enhance Self-Efficacy In Facing The Indonesian Nursing Competency Exam - Ignasia Yunita Sari; Indah Prawesti; Indrayanti Indrayanti (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2024)
Introduction: Nursing Law states that nursing students must undergo the National Competency Exam at the end of their education process. Competency testing is a process to assess knowledge, skills, and attitudes in accordance with professional standards. Strategies are needed to help students pass the competency exam. This study aims to determine whether TERBAIC is effective in improving students' self-efficacy.Method: This research is a quasi-experimental study with a post-test only nonequivalent control group design. The population consists of final-year nursing students, and the sample size in this study is 32 for the intervention group and 25 for the control group. Statistical tests used are the Wilcoxon test and Mann-Whitney test.Results: The study results indicate differences in self-efficacy before and after receiving TBL (p-value 0.00), differences in self-efficacy before and after receiving TERBAIC (p-value 0.00), and no significant difference in students' self-efficacy in facing the Indonesian National Competency Exam after receiving TBL and TERBAIC (p-value 0.887).Conclusion: TERBAIC is proven effective in enhancing self-efficacy in facing the Indonesian National Competency Exam.